Prevalence of asthma and allergic diseases in adolescents: nine-year follow-up study (2003-2012) - Dirceu Solé; Nelson A. Rosário Filho; Emanuel S. Sarinho; Inês C. Camelo-Nunes; Bruno A. Paes Barreto; Mércia L. Medeiros; Jackeline Motta Franco; Paulo A. Camargos; Javier Mallol; Ricardo Gurgel; Djanira M. de Andrade; Fernanda P. Furlan; et al. (Elsevier, 2015)
Objective: To determine the prevalence of symptoms of asthma, rhinitis, and atopic eczema in adolescents (AD; 13-14 years) living in seven Brazilian cities, by applying the standardized written questionnaire (WQ) of the International Study of Asthma and Allergies in Childhood (ISAAC), and to evaluate the time trend nine years after the last assessment of ISAAC phase 3 (ISP3). Methods: The ISAAC-WQ was answered by 20,099 AD from the Northern, Northeastern, Southeastern, and Southern Brazilian regions. Values obtained were compared to those observed in ISP3 using nonparametric (chi-squared or Fisher) tests, and the ratio of annual increment/decrement was established for each of the centers, according to the symptom assessed. Results: Considering the national data and comparing to values of ISP3, there was a decrease in the mean prevalence of active asthma (18.5% vs. 17.5%) and an increase in the frequency of severe asthma (4.5% vs. 4.7%) and physician-diagnosed asthma (14.3% vs. 17.6%). An increase in prevalence of rhinitis, rhinoconjunctivitis, and atopic eczema was also observed. Conclusions: The prevalence of asthma, rhinitis, and atopic eczema in Brazil was variable; higher prevalence values, especially of asthma and eczema, were observed in regions located closer to the Equator. Resumo: Objetivo: Determinar a prevalência de sintomas relacionados à asma, rinite e eczema atópico em adolescentes (13-14 anos, AD) residentes em sete cidades brasileiras empregando o questionário escrito (QE) padronizado do International Study of Asthma and Allergies in Childhood (ISAAC) e verificar a tendência temporal passados nove anos da última avaliação do ISAAC fase 3 (ISF3). Métodos: O QE ISAAC foi respondido por 20.099 AD (13-14 anos) moradores em centros das regiões Norte, Nordeste, Sudeste e Sul. Os índices obtidos foram comparados aos do ISF3 utilizando-se teste não paramétrico (qui-quadrado ou Fisher) e foi estabelecida a taxa de incremento/decremento anual para cada um dos centros segundo o sintoma avaliado. Resultados: Em relação ao ISF3, considerando-se os dados nacionais, houve queda da prevalência média de asma ativa (18,5% vs. 17,5%) com elevação da frequência de asma grave (4,5% vs. 4,7%) e de asma diagnosticada por médico (14,3% vs.17,6%). Aumento da prevalência de rinite e rinoconjuntivite e de eczema flexural também ocorreram. Conclusões: A prevalência de asma, rinite e eczema atópico no Brasil foi variável. Valores mais altos, sobretudo de asma e eczema foram observados nos centros localizados mais próximos ao Equador. Keywords: Asthma, Adolescent, Atopic eczema, Epidemiology, Allergic rhinitis, Rhinoconjunctivitis, Palavras-chave: Asma, Adolescente, Eczema atópico, Epidemiologia, Rinite alérgica, Rinoconjuntivite